Microbiological and bromatologic evaluation of acid silage gotten from Nile tilapia (Oreochromis niloticus) filletage industry residues - Boscolo, Wilson Rogério; Dos Santos, Ângela Maria; Martins, Cleide Viviane Buzanello; Feiden, Aldi; Bittencourt, Fábio [UNESP]; Signor, Arcangelo Augusto (Universidade Estadual de Londrina, 2010)
The experiment constituted in evaluating the acid silage prepared from Nile tilapia (Oreochromis niloticus) filletage industry residues. This silage was prepared in a filetage industry through the residues milling and 5% of ascetic acid addition and stock piling in a period up to until 201 days. Storaged silages in a period of 7, 12, 22, 27, 41, 48, 61, 75, 84, 91, 96, 110, 140, 151, 181, 187 and 201dias were evaluated. Bromatologics analyses of rude protein(PB), etereal extract (EE), humidity (UM), ashes (CZ) and microbiological analyses of Salmonella, total coliforms, faecals and Escherichia coli of the storage silages in a period of 7, 91 and 201 days were realized. The pH was evaluated in all the storaged periods. Differences (P > 0.05) in the substance of PB, EE, UM and CZ were not observed. A linear increase in PH was observed, being stabilizing in plateau of 4.74. In relation to the microbiological analysis the presence of Salmonella, total coliforms, faecals and E. Coli were not found. Was concluded that the acid silage gotten from tilapia filetage residues produced with the use of 5% ascetic acid can be stored during 201 days without having Salmonella, total coliforms and faecals proliferation.
Avaliação microbiológica e bromatológica da silagem ácida obtida de resíduos da indústria de filetagem de tilápia do Nilo (Oreochromis niloticus)
Keywords: Filletage residues; Silage stock piling